2014
DOI: 10.1055/s-0034-1383764
|View full text |Cite
|
Sign up to set email alerts
|

Patient-rated Outcomes of Lumbar Fusion in Patients with Degenerative Disease of the Lumbar Spine: Does Age Matter?

Abstract: STUDY DESIGN: Single centre retrospective study of prospectively collected data, nested within the Eurospine Spine Tango data acquisition system. OBJECTIVE: The aim of this study was to assess the patient-rated outcome and complication rates associated with lumbar fusion procedures in three different age groups. SUMMARY OF BACKGROUND DATA: There is a general reluctance to consider spinal fusion procedures in elderly patients due to the increased likelihood of complications. METHODS: Before and at 3, 12, and 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Nonetheless, few authors have analyzed complication rates of spinal surgery in general (i.e., not exclusively restricted to arthrodesis) in patients over 80, and those who did, not only have reported conflicting results but also with small sample sizes; however, spinal fusion is a more invasive surgery with respect to decompression and microdiscectomy, and in line with what other investigators have reported so far, our statistical analysis indicated that octogenarians had significantly higher rates of complications compared to individuals in their seventies or sixties for both medical and surgical complications [3,17,22,26].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Nonetheless, few authors have analyzed complication rates of spinal surgery in general (i.e., not exclusively restricted to arthrodesis) in patients over 80, and those who did, not only have reported conflicting results but also with small sample sizes; however, spinal fusion is a more invasive surgery with respect to decompression and microdiscectomy, and in line with what other investigators have reported so far, our statistical analysis indicated that octogenarians had significantly higher rates of complications compared to individuals in their seventies or sixties for both medical and surgical complications [3,17,22,26].…”
Section: Discussionsupporting
confidence: 77%
“…In surgical procedures, postoperative morbidity and mortality is historically believed to increase progressively with growing age [6,17,21,31]. Yet, this correlation does not apply uniformly for all types of surgery, and some pose the elderly at higher risk for complications than others [10].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Baseline functional limitations and lower levels of social and financial support further exacerbate postoperative outcomes. 18,19 Intriguingly, some studies have found no difference in complication rates, 20 extended LOS, 21 or reoperation rates 21 for octogenarians compared to younger patients following spine surgery, throwing into question the idea that older patients inherently will have worse surgical outcomes. For our study, it is possible that only particularly healthy elderly patients with an extended life expectancy were deemed fit enough to undergo surgical intervention and thus had lower readmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…With population aging, the number of patients with degenerative lumbar disease, such as lumbar spinal stenosis, lumbar instability and lumbar disc herniation, has increased each year, severely affecting people's quality of life. 1,2 For cases that do not respond to conservative treatment, surgical treatment is often required. Pedicle screw fixation is considered the gold standard surgical treatment for lumbar degeneration.…”
Section: Introductionmentioning
confidence: 99%